Sex-Specific Association of Left Ventricular Hypertrophy With Rheumatoid Arthritis - Giollo, Alessandro; Cioffi, Giovanni; Ognibeni, Federica; Bixio, Riccardo; Fassio, Angelo; Adami, Giovanni; Orsolini, Giovanni; Dalbeni, Andrea; Idolazzi, Luca; Gatti, Davide; Rossini, Maurizio; Viapiana, Ombretta (Frontiers in Cardiovascular Medicine, 2021)
Objectives. Clinical expression of rheumatoid arthritis (RA) varies by gender, but whether cardiovascular disease (CVD) is gender-related in RA is unknown. Left ventricular (LV) hypertrophy (LVH) is a hallmark of CVD in RA patients. We investigated whether the association of LVH with RA is gender-driven. Methods. Consecutive outpatients with established RA underwent echocardiography with measurement of LVH at baseline and one follow-up. All participants had no prior history of CVD or diabetes mellitus. We assessed CVD risk factors associated with LVH at follow-up, including sex, age, arterial blood pressure, and body mass index (BMI). We also evaluated inflammatory markers, autoimmunity, disease activity, and the use of RA medications as predictors of LVH. Results. We recruited 145 RA patients (121 females, 83%) and reassessed them after a median [interquartile range] of 36 [24-50] months. At baseline, women were more dyslipidaemic but otherwise had fewer CVD risk factors than men, including less prevalent smoking habit and hypertension, and smaller waist circumference. At follow-up, we detected LVH in 42/145 (44%) RA patients. LV mass significantly increased only in women. In multiple Cox regression analysis, women with RA had the strongest association with LVH, independently from the presence of CVD risk factors (OR 6.56; 95% CI 1.34-30.96) or RA-specific characteristics (OR 5.14; 95% CI 1.24-21.34). BMI was also significantly and independently associated with LVH. Conclusion. Among established RA patients, women carry the highest predisposition for LVH.